Parametric study on structural behavior of tubular K-joints under axial loading at fire-induced elevated temperatures. (September 2018) - Azari Dodaran, Neda; Ahmadi, Hamid; Lotfollahi-Yaghin, Mohammad Ali
Abstract: Present research used the results of 405 finite element (FE) analyses to study the effect of the joint geometry on the ultimate strength and initial stiffness of tubular K-joints subjected to axial loading at fire-induced elevated temperatures. The FE models were validated against the data available from experimental tests. Structural behavior under different temperatures (200 °C, 400 °C, 500 °C, and 700 °C) was investigated and compared to the behavior at ambient temperature (20 °C). Results showed that by increasing the temperature, the ultimate strength and initial stiffness may decrease drastically. On average, the reduction of ultimate strength is 5%, 19%, 51%, and 83% at 200 °C, 400 °C, 550 °C, and 700 °C, respectively. A parametric study was conducted to investigate the effect of dimensionless geometrical parameters ( β, γ, θ, and τ ) on the ultimate strength and initial stiffness. Afterwards, ultimate strength data extracted from the FE analyses was compared with the values calculated from the equations proposed by available design codes in which the ultimate strength of the joint at elevated temperatures is obtained by replacing the yield stress of the steel at ambient temperature with the corresponding value at elevated temperature. It was indicated that this method may not have acceptable accuracy for carbon steel K-joints under axial loading. Hence, a new design formula was developed, through nonlinear regression analyses, to determine the ultimate strength of K-joints subjected to balanced axial loads at elevated temperatures. Highlights: Ultimate strength of tubular K-joints at elevated temperatures was studied. Reduction of ultimate strength was 51% and 83% at 550 ºC and 700 ºC, respectively. A new design formula was developed to determine the ultimate strength of K-joints.